Using Public Speaking To Improve Malaysian Students’ Confidence Level In Speaking Skill: A Case Study - Adnan, Nur Ilianis (2014)

(untitled)
Public Speaking is one of the ways to improve Malaysian students’ speaking skill. Through a widespread literature review, it is shown that public speaking improves students’ confidence level and speaking skill. This is because the programme offers them the opportunity to improve the fluency of their speeches and their confidence level in terms of body language, vocal variety, hand gestures, facial expressions and eye contact. This study with a case study design was conducted to study the effectiveness of Public Speaking Programme in improving Malaysian students’ confidence level in speaking skill. Pengucapan awam merupakan salah satu cara untuk meningkatkan kemahiran bertutur. Berdasarkan kajian literatur yang meluas, didapati bahawa pengucapan awam dapat meningkatkan tahap keyakinan pelajar dan kemahiran bertutur. Hal ini adalah kerana program ini menawarkan peluang kepada mereka untuk meningkatkan kelancaran ucapan-ucapan mereka dan tahap keyakinan mereka dari segi bahasa badan, kepelbagaian vokal, isyarat tangan, ekspresi muka dan mata. Kajian kes ini dijalankan untuk mengkaji keberkesanan program pengucapan awam dalam meningkatkan tahap keyakinan pelajar Malaysia dalam kemahiran bertutur.